2019
DOI: 10.1111/acer.14193
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Alcohol Intake During Pregnancy in Spain, 1980 to 2014

Abstract: Background Even small amounts of alcohol consumed during pregnancy can have adverse effects on the embryo and the fetus. We estimated how alcohol intake among pregnant women in Spain changed between 1980 and 2014, and identified factors associated with alcohol use. Methods Data came from the Spanish Collaborative Study of Congenital Malformations (ECEMC). The sample includes ECEMC′s control mothers, 40,268 pregnant women from all regions of Spain. We classified alcohol consumption during pregnancy into 3 categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…28 However, it is important to note that there is conflicting evidence regarding the prevalence of alcohol use during preg nancy over time. Some studies have indicated a decrease in alcohol use during pregnancy over time, 29 whereas others have pointed to an increase. 30 From 2015 -2021, there was an increase in the studies focusing on biomarkers and the accuracy of selfreport measures compared to various biological measures of alcohol use (e.g., meconium samples, urine toxicology, blood samples, alcohol metabolite analysis).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 However, it is important to note that there is conflicting evidence regarding the prevalence of alcohol use during preg nancy over time. Some studies have indicated a decrease in alcohol use during pregnancy over time, 29 whereas others have pointed to an increase. 30 From 2015 -2021, there was an increase in the studies focusing on biomarkers and the accuracy of selfreport measures compared to various biological measures of alcohol use (e.g., meconium samples, urine toxicology, blood samples, alcohol metabolite analysis).…”
Section: Methodsmentioning
confidence: 99%
“…There are a wide range of factors and influ ences that impact women's alcohol use during pregnancy, including pregnancy recognition, 35 knowledge of FASD 36 and/or the impacts of alcohol use during pregnancy, 20,23,[36][37][38] marital status, 22,39 planned pregnancy, 23,24,29.35.37.38.40.41 tobacco 20,26,35,39 and other/polysubstance use during the preconcep tion and pregnancy periods, 24,29,41,42 and preconcep tion alcohol use, including preconception binge drinking. 32,39 Alcohol use in pregnancy was also influenced by adverse childhood experiences, 43,44 trauma, 45,46 residential school histories, 47 and mental health status.…”
Section: Factors Associated With Alcohol Use In Pregnancymentioning
confidence: 99%